Rape culture and spiritual violence : religion, testimony, and visions of healing - Messina-Dysert, Gina (Abingdon, Oxon : Routledge, Taylor & Francis Group, 2015)
This volumes examines sexual violence against women and how religion and society contribute to a rape culture as well as the extreme suffering endured by rape victims as a result.
Introduction -- Rape culture ordained by God? -- Learning from women's testimony -- A preliminary analysis of sexual violence and rape culture -- Sexual violence, han, and spiritual death -- Spiritual resurrection : Han-Pu-Ri and momentary salvation -- Conclusion.
Includes bibliographical references (pages [116]-124) and index.
Keywords: Rape -- Social aspects; Rape -- Religious aspects; Rape victims